Sistem Informasi Pengelolaan Freelancer pada Playcubic Berbasis WEB - Pratama, Kevin; Kusumawati, Arie (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
Playcubic is a start-up business enganged in mass media industry. The system that Playcubiccurrently use is still using traditional system. The system used to have the risk of losing data and fakeddata. This study aims to help business including process of uploading article, invitation sharing andpayroll sytem for freelancer. The system under development method is using prototype developmentmethod. The results of this study are an information system that can be used by Playcubic that havebeen tested with black box testing.